Effect of focal muscle vibration on flexibility and perceived stiffness in patients with mechanical low back pain - Mirza Obaid Baig; Maham Malik; Anam Pervez Qureshi; Abdul Wasay Nafe; Zarlish Ayan; Aqsa Liaquat (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Low back pain is a major disabling pathology worldwide. A focal muscle vibrator can be a treatment option for reducing pain in such patients. The objective of this study was to determine the effects of focal muscle vibration on flexibility, perceived stiffness and pain intensity in patients with mechanical low back pain. METHODOLOGY: A randomized clinical trial was conducted at Railway General Hospital Rawalpindi. Reviewing the limited number of studies done using focal muscle vibrator for low back pain, 44 participants were randomly divided into two groups. The experimental group received a focal muscle vibrator and physical therapy treatment, while the control group received conventional physical therapy treatment. Sessions were planned thrice a week for a total of four weeks. Baseline data was recorded at the start, with a final recording at the end of the fourth week for pain, muscle soreness and flexibility. RESULTS: A total of 44 patients with mechanical low back pain aged between 25 to 45 years were recruited. Both groups showed improvement in pain, muscle soreness and flexibility, but there was a significant improvement in pain and flexibility in the experimental group (p≤0.05). There was no significant difference noted in muscle soreness in between group analysis (p≥ 0.05). CONCLUSION: Focal Muscle Vibrator (myovolt 120 Hz frequency) along with Physiotherapy protocol is effective in improving pain and flexibility of mechanical low back pain patients, but muscle soreness showed less significant improvement in both groups, while between the groups analysis showed no significant statistical difference.